Answer:
9(t+5)<6
t<-13/3
Step-by-step explanation:
The expression is 9(t+5)<6
Distributing the 9, we get
9t+45<6
9t<-39
t<-13/3
we have that
Applying proportion
x/9=5.5/3
solve for x
x=9*(5.5/3)
x=16.5 ft
therefore
<h2>the answer is 16.5 ft</h2>
Answer:
3. x-2
Step-by-step explanation:
Let's start with 1. we know that 2-x is the same as -2+x and since addition can be written as -2+x or x+(-2) and equal the same thing, we know that x-2 is the one that is not equivalent.
Answer: -8
Explanation: If g(x) = x² + 2x - 8, then g(-2) = (-2)² + 2(-2) - 8
which simplifies to 4 + (-4) - 8 or 0 - 8 which is -8.
Remember to always use parentheses when
substituting your given value in for <em>x</em>.
Answer:
Step-by-step explanation:
6A = 60°
6B = 34°